A comprehensive review on engineered microbial production of farnesene for versatile applications - Rautela A.; Chatterjee R.; Yadav I.; Kumar S. (My University, 2025)
In the current energy paradigms, most of the requirements, be it fuel for transportation, electricity generation, or thermoplastic materials production, are fulfilled by utilizing fossil-based fuels such as coal, petroleum, and natural gases. This leads to the generation of substantial amounts of greenhouse gases into the atmosphere causing global warming. Besides this, ceaseless administration of insecticides/pesticides to feed the expanding population not only pollutes the environment but also leads to biomagnification. Terpenoids are naturally produced by plants, and among them, farnesene, an important sesquiterpenoid, is a versatile candidate for applications such as biofuel, insecticides or pesticides, thermoplastic elastomers, medicine, cosmetics, and flavorings. Chemical synthesis and extraction of farnesene from plant sources is not sustainable and is expensive compared to microbial synthesis. Consequently, to decouple the carbon growth and market demand, there is a greater reliance on the biological sector. This review article expounds on recent advances in metabolic engineering strategies employed by microbial cell factories for farnesene production. Additionally, it offers insights into the challenges and shortcomings of transitioning engineered strains from lab scale to industry. Further, numerous applications of farnesene and its derivatives are thoroughly investigated in the field of biofuel, to be used for crop protection, as an alternative to thermoplastic elastomers, its pharmacological relevance, and other miscellaneous applications such as skin-whitening agent, flavorant in e-cigarettes, and production of vitamin E. © 2024 Elsevier Ltd